Hubungan Perilaku Orang Tua Dan Faktor Lingkungan Dengan Kejadian Tuberkulosis Paru Pada Anak Di Desa Bangunjaya Tahun 2020: Relationship Between Parental Behavior and Environmental Factors with The Incidence of Pulmonary Tuberculosis in Children in Bangunjaya Village in 2020 - Nurmalinda Noviansyah; Nur Eni Lestari; Eka Rokhmiati (Dohara POAJ, 2021)
Introduction: Parental Behavior, and Environmental Factors are closely related, and affect children's health. Methods: The research design used was analytical correlation with cross-sectional correlation or cross-sectional approach. The cross-sectional correlation approach is an approach that is momentary at one time, and aims to study whether there is a relationship between risk factors (independent variables) and effects (dependent variables) that are observed at the same time as Notoatrnodjo (2010). In this study, the factors for the occurrence of pulmonary tuberculosis in children in Bangunjaya Village were looked for in 2020. Results: The behavior of parents with the incidence of pulmonary tuberculosis in children in Bangunjaya village in 2020 obtained a negative category 33 (61.1%), and a positive category 21 (39.9%). Environmental factors with the incidence of pulmonary tuberculosis in children in Bangunjaya village in 2020 obtained good category 47 (87.0%), and less category 7 (13.0%). Discussion: There is a relationship between parental behavior and environmental factors with the incidence of pulmonary tuberculosis in children in Bangunjaya village in 2020.